ANALISIS STRATEGI GURU DALAM MENGINTEGRASIKAN KONSEP DASAR MATEMATIKA DENGAN KEHIDUPAN SEHARI-HARI SISWA KELAS II SDN 03 BANDAR BUAT - Sakina Oktari, Ridha; Salmaini , Salmaini; Nisa, Sahrun; Putri Zulkarnaini, Aissy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze teacher strategies in integrating basic mathematics concepts of plane and solid shapes with the daily lives of second-grade elementary school students. The research employed a qualitative approach with a case study method. The subjects were a second-grade teacher and three students with different ability levels (high, medium, low) at SDN 03 Bandar Buat. Data were collected through observation, in-depth interviews, and documentation, then analyzed using Miles and Huberman data analysis techniques. The results show: (1) in the preparation stage, teachers prepare teaching modules, select concrete media, and plan varied methods; (2) in the implementation stage, teachers use contextual apperception, manipulative media, interactive questioning methods, and gradual learning; (3) obstacles include differences in student abilities, limited media, and lack of parental participation; (4) teacher efforts include individual approaches, use of real objects, and continuous assessment; (5) evaluation is conducted through observation, questioning, assignments, and presentations. The use of concrete media and connection to daily life proved effective in improving students' understanding of geometry concepts, although mastery levels vary according to individual abilities.